IMPACT OF EXPANDED LEGAL LIABILITY ON HOSPITAL OPERATIONS AND MANAGEMENT - Gunawan Widjaja; Dyah Ersita Yustanti (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
The expansion of legal liability on hospitals has brought about significant changes in the operations and management of these healthcare institutions. This discussion explores how increased legal liability affects regulatory compliance, quality of care, administrative burden, and risk management strategies. The findings show that while there are positive impacts in the form of improved service quality and patient safety, hospitals also face challenges in the form of increased administrative and operational burdens. In addition, hospital management is forced to implement more comprehensive risk management strategies to manage potential legal issues. In conclusion, while the expansion of legal liability creates challenges for hospital management and operations, it also contributes to the overall improvement of healthcare standards and patient safety.